Effect of water level and factor of safety to slope stability : a case study on Beris Dam, Kedah - Saedah @ Saedatulfirdaus Sa'arani; Nazri Ali, supervisor; Fakulti Kejuruteraan Awam (2010)
Project Paper (Sarjana Muda Kejuruteraan (Awam - Geoteknik)) - Universiti Teknologi Malaysia, 2010